Diabetes Educators' Intended and Reported Use of Common Diabetes-Related Technologies: Discrepancies and Dissonance. (November 2016) - James, Steven; Perry, Lin; Gallagher, Robyn; Lowe, Julia
Background: Technology provides adjuvant and/or alternative approaches to care and may promote self-care, communication, and engagement with health care services. Common recent technologies for diabetes include continuous subcutaneous insulin infusions (insulin pumps), continuous glucose monitoring systems, smartphone and tablet applications, and telehealth (video conferencing). This study reports Australian diabetes educators' intentions and reported professional use of these technologies for people with type 1 diabetes, and factors predictive of this. Methods: An anonymous, web-based questionnaire based on the technology acceptance model was distributed to members of the Australian Diabetes Educators Association through their electronic newsletter. Exploratory factor analysis revealed a 5-factor solution comprising confidence and competence, improving clinical practice, preparation (intentions and training), ease of use, and subjective norms. Logistic regression analyses identified factors predicting intention and use of technology. Results: Respondents (n = 228) had high intentions to use technology. The majority reported using continuous subcutaneous insulin infusions, continuous glucose monitoring systems, and applications with patients, but usage was occasional. Confidence and competence independently predicted both intentions and use of all 4 technologies. Preparation (intentions and training) independently predicted use of each technology also. Conclusions: Discrepancies and dissonance appear between diabetes educators' intentions and behavior (intentions to use and reported technology use). Intentions were higher than current use, which was relatively low and not likely to provide significant support to people with type 1 diabetes for disease management, communication, and engagement with health care services. Continuing education and experiential learning may be key in supporting diabetes educators to align their intentions with their practice.